miR-889-3p targeting BMPR2 promotes the development of retinoblastoma via JNK/MAPK/ERK signaling - Yuan Gao; Pei Du (Scientific Reports, 2024)
Abstract MicroRNAs (miRNAs) are vital regulators of tumor pathogenesis, including that of retinoblastoma (Rb). This study investigated the functions and mechanisms of action of miR-889-3p in Rb. BMPR2 and miR-889-3p levels were assessed by quantitative reverse transcription PCR (qRT-PCR) or western blotting. Through several cell function tests, the effects of miR-889-3p and BMPR2 on cell proliferation, migration, and JNK/MAPK/ERK signaling were evaluated. The interaction between miR-889-3p and BMPR2 was investigated using a luciferase reporter assay. In vivo tumor development was investigated using a xenograft test. The association between miR-889-3p and BMPR2 expression was identified using Pearson’s correlation analysis. miR-889-3p was increased in Rb cells, and miR-889-3p knockdown inhibited Rb cell proliferation, migration, and phosphorylation of c-Jun N-terminal kinase (JNK), p38 mitogen-activated protein kinase (MAPK), and ERK1/2 in vitro, as well as tumor growth in vivo. Further, they were inversely associated in Rb tissues and miR-889-3p may directly attached to the 3′-UTR of BMPR2 mRNA. Finally, the inhibition of BMPR2 inverted the negative effects of the miR-889-3p inhibitor on migration, proliferation, and activation of JNK, p38 MAPK, and ERK1/2 in Rb cells. Our results indicate that miR-889-3p, which targets BMPR2 and promotes Rb growth by controlling the JNK/MAPK/ERK pathway, is an oncogene in Rb. These results suggested that the miR-889-3p/BMPR2 axis may be a new therapeutic target for Rb.